Surgical treatment of acute endocarditis of the aortic valve with paravalvular abscess: considerations justifying the use of mechanical replacement devices - Bauernschmitt, Robert; Vahl, Christian-Friedrich; Lange, Rüdiger; Jakob, Heinz; Hagl, Siegfried (European journal of cardio-thoracic surgery, 1996)
OBJECTIVE: Early recurrency after surgery for acute endocarditis is a life-threatening complication. Allograft valves are supposed to have a higher resistance to recurrent infection, thus several authors claim them to be the replacement device of choice in cases of aortic endocarditis. However, allografts have two major drawbacks: their availability is limited, and most of the patients require reoperation for graft calcification of degeneration. Until now there has been no prospective study analysing whether early recurrency after surgery of acute endocarditis is associated with the mechanical valve per se or with factors related to the surgical technique or postoperative care. - PATIENTS AND METHODS: We present a prospective study on 36 consecutive patients with acute endocarditis of the aortic valve with paravalvular abscesses. In this series, there were 5 women and 31 men with a mean age of 50.3 years. All patients were operated before a course of antibiotic therapy was completed. Abscesses were radically resected and the cavities closed either with direct suture or, if not possible, with Dacron patches. For aortic valve replacement, a mechanical valve was used in every patient. - RESULTS: The early mortality in this series was 14%, only one patient experienced recurrent endocarditis and underwent reoperation. The results compare well with those achieved after valve replacements with allograft valves. - CONCLUSION: We conclude that, even in cases of acute endocarditis, replacement of the aortic valve with a mechanical device is an acceptable alternative to the allograft, if radical surgical debridement and adequate antibiotic therapy are performed.
Gesehen am 16.06.2025